The The Presentation Quality of Indonesian High School History Textbooks During the New Order Administrative and After (1975-2008) - Victor Novianto; Hieronymus Purwanta; Bayu Ananto Wibowo (Diakronika, 2022)
This study aimed to analyze the presentation quality of history textbooks used for the national curriculum 1975-2008. The function of the Presentation is to develop students' independent learning. The method used in this study is content analysis. Contents of the history textbooks were analyzed and assessed for presentation aspects using the textbook criteria developed by the Board of National Standards for Education. The result shows that attention for Presentation began on history textbooks for the 1984 curriculum and grew in the following periods of curriculums. The presentation aspects of the history textbook achieved their peak on the 2006 curriculum, where the Board established textbook criteria in selecting textbooks for Indonesian schools. One of the criteria was presentation aspects